Macierzyństwo nastoletnich kobiet w aspekcie społecznym, psychologicznym i prawnym = Childbearing among teenage women as seen from the social, psychological and legal points of view - Agnieszka Bałanda-Bałdyga; Celina Łepecka-Klusek; Anna Bogusława Pilewska-Kozak; Agnieszka Konstancja Pawłowska-Muc; Grażyna Stadnicka (Journal of Education, Health and Sport, 2016)
Bałanda-Bałdyga Agnieszka, Łepecka-Klusek Celina, Pilewska-Kozak Anna B., Pawłowska-Muc Agnieszka K., Stadnicka Grażyna. Macierzyństwo nastoletnich kobiet w aspekcie społecznym, psychologicznym i prawnym = Childbearing among teenage women as seen from the social, psychological and legal points of view. Journal of Education, Health and Sport. 2016;6(6):531-542. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.56481